Killing acanthamoebae with polyaminopropyl biguanide: quantitation and kinetics. - Burger, R M (1994)
The two Acanthamoeba species most often implicated in corneal keratitis, A. castellanii and A. polyphaga, were exposed as cysts to polyaminopropyl biguanide (PAPB), a commonly used antimicrobial agent. Killing of amoeba cysts was rapid and extensive, with fewer than 2% of either species surviving 30 s of exposure to > or = 45 ppm of PAPB. Killing kinetics were biphasic, and further exposures of 15 min to 1 h killed greater than 90% of those surviving initial killing. This potency of PAPB, together with its low toxicity to humans when ingested or applied topically, underscores the potential of PAPB as an antiamoebic agent.